Design, Synthesis and Evaluation of Diphenyl ether Derivatives as Antitubercular and Antibacterial Agents - Sari S Nair; Cinu Thomas A; Anjali T; Vineetha S (International Journal of Pharmacy and Analytical Research, 2020)
A new series of diphenyl ether derivatives were synthesized from meta phenoxy benzaldehyde and aniline. The synthesized compounds were screened for in-vitro antimycobacterial, antibacterial and cytotoxicity studies. The synthesized compound 2a have shown potential activity against Mycobacterium tuberculosis H37Rv strain with MIC 12.5. These diphenyl ether derivatives were subjected to docking studies and virtual screening. The receptor specificity of the synthesized compounds were shown from the antibacterial activity study since none of the synthesized compounds showed activity, so it have been proved that newly synthesized compounds were specifically act on the enoyl acyl carrier protein receptor.